Hif-1α Knockdown Reduces Glycolytic Metabolism and Induces Cell Death of Human Synovial Fibroblasts Under Normoxic Conditions - Manuel J. Del Rey (Nature Portfolio, 2017)
Abstract Increased glycolysis and HIF-1α activity are characteristics of cells under hypoxic or inflammatory conditions. Besides, in normal O2 environments, elevated rates of glycolysis support critical cellular mechanisms such as cell survival. The purpose of this study was to analyze the contribution of HIF-1α to the energy metabolism and survival of human synovial fibroblasts (SF) under normoxic conditions. HIF-1α was silenced using lentiviral vectors or small-interfering RNA (siRNA) duplexes. Expression analysis by qRT-PCR and western blot of known HIF-1α target genes in hypoxia demonstrated the presence of functional HIF-1α in normoxic SF and confirmed the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a HIF-1α target even in normoxia. HIF-1α silencing induced apoptotic cell death in cultured SF and, similarly, treatment with glycolytic, but not with OXPHOS inhibitors, induced SF death. Finally, in vivo HIF-1α targeting by siRNA showed a significant reduction in the viability of human SF engrafted into a murine air pouch. Our results demonstrate that SF are highly dependent on glycolytic metabolism and that HIF-1α plays a regulatory role in glycolysis even under aerobic conditions. Local targeting of HIF-1α provides a feasible strategy to reduce SF hyperplasia in chronic arthritic diseases.